The Himalaya : environment, economy, and society - Pal, Anindya (New Delhi : Vikas, 1995)
Contributed articles.
Includes bibliographical references and index.
Keywords: Natural resources -- Himalaya Mountains; Environmental policy -- Himalaya Mountains; Himalaya Mountains -- Economic conditions